2021
DOI: 10.29333/ejecs/855
|View full text |Cite
|
Sign up to set email alerts
|

A Time-Lag Study on Perceived Threat of COVID-19 in Hindu Religious Community: Moderating Role of Hindu Religious Coping

Abstract: The COVID-19 pandemic had a serious impact on developing various psychological stressors in society. Grounded in cognitive appraisal theory, the current study has been conducted to investigate the moderating role of Hindu religious coping in mitigating the impact of the perceived threat of COVID-19 in developing perceived stress, insomnia, anxiety, and depression among the Hindu residents in Bali, Indonesia. The current study contributed to the body of knowledge regarding religious practices acting as a coping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 78 publications
(102 reference statements)
1
2
0
Order By: Relevance
“…Mills and colleagues describe the Thai culturally embedded coping strategy of acceptance ('Thum-jai') as "accepting and letting go of the negative situation, forgetting the bad feeling, calming or steadying the mind, and developing patience and understanding" [86], finding that the emotion-based coping strategy of 'Thum-jai' helped Thai people develop purposeful approaches of thinking and acting in light of adverse events which cannot be changed [87]. Our findings also echo other research on the positive association between social support and coping from Thailand (e.g., HIV [88], breast cancer [89,90] and COVID-19 [91]) and internationally (e.g., religious coping in the context of COVID-19 [92][93][94][95], healthy ageing [96] and terminal illness [97]), highlighting the important and beneficial role of spirituality and religion in coping with adverse health events and crises. Similarly, a qualitative study examining mental health impacts and coping strategies among disadvantaged groups in India during COVID-19 lockdown found that religion and devotional practices played an important role in participants coping strategies, by helping them make sense and find meaning in the COVID-19 crisis.…”
Section: Copingsupporting
confidence: 84%
“…Mills and colleagues describe the Thai culturally embedded coping strategy of acceptance ('Thum-jai') as "accepting and letting go of the negative situation, forgetting the bad feeling, calming or steadying the mind, and developing patience and understanding" [86], finding that the emotion-based coping strategy of 'Thum-jai' helped Thai people develop purposeful approaches of thinking and acting in light of adverse events which cannot be changed [87]. Our findings also echo other research on the positive association between social support and coping from Thailand (e.g., HIV [88], breast cancer [89,90] and COVID-19 [91]) and internationally (e.g., religious coping in the context of COVID-19 [92][93][94][95], healthy ageing [96] and terminal illness [97]), highlighting the important and beneficial role of spirituality and religion in coping with adverse health events and crises. Similarly, a qualitative study examining mental health impacts and coping strategies among disadvantaged groups in India during COVID-19 lockdown found that religion and devotional practices played an important role in participants coping strategies, by helping them make sense and find meaning in the COVID-19 crisis.…”
Section: Copingsupporting
confidence: 84%
“…Still, fewer have focused on using religious values by government officials to address safety and wellbeing issues during the pandemic. Additionally, religious values' role in gaining and maintaining citizens' trust in uncertain and crisis circumstances has not been explored in previous literature related to public trust, e-governance, or Covid-19 (Sueca et al, 2021). Therefore, to bridge this existing gap in the literature, the current study examined the mediatory role of perceived religious value between the association of interaction with government officials on SNS, Perceived egovernance effectiveness, and government response Covid-19 with overall public trust in government.…”
mentioning
confidence: 99%
“…Indonesia's school closure policy during the COVID-19 pandemic has left 45.5 million school students and 3.1 million teachers dependent on online teaching and learning (Almanthari et al, 2020;Daud, 2020). Based on the results of the study by Sueca et al (2021), it was concluded that COVID-19 had a serious impact on high levels of stress, insomnia, anxiety, and depression. This condition can increase the gap in student achievement between the economically capable and the less fortunate compared to the period before the pandemic (Bailey et al, 2021).…”
mentioning
confidence: 99%